Adoption of multiple climate-smart agricultural practices in the Gangetic plains of Bihar, India - Aryal, Jeetendra Prakash; Jat, Mangi Lal; Sapkota, Tek Bahadur; Khatri-Chhetri, Arun; Kassie, Menale; Rahut, Dil Bahadur; Maharjan, Sofina (Emerald Publishing Limited, 2018)
The adoption of climate-smart agricultural practices (CSAPs) is important for sustaining Indian agriculture in the face of climate change. Despite considerable effort by both national and international agricultural organizations to promote CSAPs in India, adoption of these practices is low. This study aims to examine the elements that affect the likelihood and intensity of adoption of multiple CSAPs in Bihar, India. Design/methodology/approach The probability and intensity of adoption of CSAPs are analyzed using multivariate and ordered probit models, respectively. Findings The results show significant correlations between multiple CSAPs, indicating that their adoptions are interrelated, providing opportunities to exploit the complementarities. The results confirm that both the probability and intensity of adoption of CSAPs are affected by numerous factors, such as demographic characteristics, farm plot features, access to market, socio-economics, climate risks, access to extension services and training. Farmers who perceive high temperature as the major climate risk factor are more likely to adopt crop diversification and minimum tillage. Farmers are less likely to adopt site-specific nutrient management if faced with short winters; however, they are more likely to adopt minimum tillage in this case. Training on agricultural issues is found to have a positive impact on the likelihood and the intensity of CSAPs adoption. Practical implications The major policy recommendations coming from of our results are to strengthen local institutions (public extension services, etc.) and to provide more training on CSAPs. Originality/value By applying multivariate and ordered probit models, this paper provides some insights on the long-standing discussions on whether farmers adopt CSAPs in a piecemeal or in a composite way.